Renal insufficiency predicts worse prognosis in newly diagnosed IgD multiple myeloma patients - Yan, Ge; Li, Huangmin; Zhang, Yiding; Xia, Chenyan; Wang, Mengxiao; Jia, Yu; Shang, Jin; Zhao, Zhanzheng (Frontiers in Oncology, 2022)
OBJECTIVE: IgD multiple myeloma (MM) is a rare type of MM, accounting for about 1%–2% of all MMs. IgD MM always causes kidney damage and even leads to renal failure, which is the most common complication. This study aimed to explore the risk factors of renal damage and prognosis of IgD MM patients. DESIGN: From March 2018 to November 2021, 85 patients with IgD MM diagnosed for the first time were included in this study. We collected information on clinical features and laboratory examinations. Patients were divided into the renal impairment (RI) (47/85) and non-renal impairment (no-RI) (38/85) groups. Binary logistic regression was used to explore risk factors of renal damage. The Chi-square test was used to analyze the difference in chemotherapy effect between the two groups. We also analyzed whether early dialysis was beneficial to acute renal failure (RF) in IgD MM patients. Finally, Kaplan-Meier was used to compare the survival of the two groups. RESULTS: In IgD MM, 55.3% of patients had renal damage as a complication, of which up to 59.6% presented with acute renal failure as the first manifestation. Serum β2-microglobulin (β2-MG) was an independent risk factor for renal damage in IgD MM (p = 0.002), but cytogenetic analysis suggested that it had no effect on patients’ renal damage. There was also no significant difference in the effect of chemotherapy between the two groups (p = 0.255). In patients with acute renal failure, there was no significant difference between dialysis and no dialysis groups in the proportion of patients with improved renal function after treatment. The median overall survival (OS) of the RI group was significantly shorter than that of the no-RI group (p = 0.042). In the RI group, the median OS was 29 months, and in the no-RI group, the median OS was > 40 months. CONCLUSION: Serum β2-MG is an independent risk factor for renal damage. Compared with the no-RI group, patients in the RI group had poorer prognosis and shorter median OS. For patients with acute renal failure as the first manifestation, the treatment of primary disease is more meaningful than dialysis.